2021
DOI: 10.3390/antiox11010022
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Lipid Droplets in Neuroglia

Abstract: In recent years, increasing evidence regarding the functional importance of lipid droplets (LDs), cytoplasmic storage organelles in the central nervous system (CNS), has emerged. Although not abundantly present in the CNS under normal conditions in adulthood, LDs accumulate in the CNS during development and aging, as well as in some neurologic disorders. LDs are actively involved in cellular lipid turnover and stress response. By regulating the storage of excess fatty acids, cholesterol, and ceramides in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 218 publications
(339 reference statements)
0
21
0
Order By: Relevance
“… 86 The mechanism by which excess lipid droplets accumulate in ependymal cells and the implications of retaining excess lipids with respect to the neuropathology of Alzheimer’s disease in humans is yet to be elucidated. 87 Similar to multiple sclerosis, widespread neuroinflammation and oxidative stress are also key factors in the pathogenesis of Alzheimer’s disease and may cause ependymal cells to become pathogenic as a result of their sensitivity to inflammation, 88 though this has been more broadly studied in glial cells.…”
Section: Ependymal Cell Dysfunction In Neurodegenerative Diseasementioning
confidence: 99%
“… 86 The mechanism by which excess lipid droplets accumulate in ependymal cells and the implications of retaining excess lipids with respect to the neuropathology of Alzheimer’s disease in humans is yet to be elucidated. 87 Similar to multiple sclerosis, widespread neuroinflammation and oxidative stress are also key factors in the pathogenesis of Alzheimer’s disease and may cause ependymal cells to become pathogenic as a result of their sensitivity to inflammation, 88 though this has been more broadly studied in glial cells.…”
Section: Ependymal Cell Dysfunction In Neurodegenerative Diseasementioning
confidence: 99%
“…Additionally, neutral lipids were significantly reduced in the DN relative to the DD COs ( Fig 6A–6C ). Given that neutral lipids are packaged in lipid droplets (LDs) for further utilization in beta-oxidation and gluconeogenesis [ 24 , 25 ], we assessed the LDs in the COs and found significantly lower LDs in the DN COs relative to the controls ( Fig 6D and 6E ). Given that in the process of beta oxidation, mitochondria are recruited toward the LDs to facilitate the use of neutral lipids [ 24 ], we assessed the mitochondria and LD-like compartments localization in astrocytes by TEM.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies would also benefit from characterising the functional capacity of these associated enzymes. Finally, it has been reported that ALS patients are prone to cholesterol droplet build-up [25] and whilst this has most commonly been attributed to astrocytes to date, cholesterol droplets have also been identified in oligodendrocytes [26]. Increased cholesterol has previously been reported in ALS (in human CSF [27], human spinal cord ventral horn [28] and the spinal cord of SOD1 mutant mice [17,28]); our data suggest that oligodendrocytes and myelin may also contribute to altered cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%